If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 5c + -1a + 2c = 0 Reorder the terms: 3a + -1a + 5c + 2c = 0 Combine like terms: 3a + -1a = 2a 2a + 5c + 2c = 0 Combine like terms: 5c + 2c = 7c 2a + 7c = 0 Solving 2a + 7c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7c' to each side of the equation. 2a + 7c + -7c = 0 + -7c Combine like terms: 7c + -7c = 0 2a + 0 = 0 + -7c 2a = 0 + -7c Remove the zero: 2a = -7c Divide each side by '2'. a = -3.5c Simplifying a = -3.5c
| 16x^2-44x-32=0 | | 15x-3=24+6x | | 15x-3=24+3 | | 7/6·x=2 | | (-B^2+3)(B^2-6)= | | 49-7a= | | -3c^2-3c-36=0 | | 3(x-6)-4(3x-5)=9 | | A=(1/2)b-4 | | (x^2-15)^(3/2)=0 | | 5u^2-11u-12=0 | | (1/2)cosine3 | | 7x+-28= | | A=4+6(5-4) | | X^2-(m-2)x+2m=0 | | N-1/5=4 | | 12=b+6(7-2) | | A=6+4(5-4) | | 25-3(4.75)= | | 64x^2+16y^2=81 | | 2×4(6/3)-5= | | 5(z-3)=7(z-5) | | 19=4Q | | 11=5+3(4-2) | | 34/30 | | 2(x+15)=3(x+1) | | 2×4(6/3)-5 | | 4(3k-7)=(3k-2) | | 2x4(6/3)-5 | | 78=3Q | | 5x-2=12x-84 | | 5(2h-3)=5h+10 |